Effects of experimental warming on nitrogen concentration and biomass of forage plants for an arctic herbivore. (17th January 2014) - Doiron, Madeleine; Gauthier, Gilles; Lévesque, Esther; Newman, Jonathan
Summary In many arctic herbivores, the growth of young depends upon a synchrony between hatching date and seasonal change in plant nutritive quality. If plants respond more quickly than herbivores to climate warming, this may cause a mismatch between the availability of high‐quality food and the hatching of young. This study examines the impact of experimental warming on the main food plants of an arctic herbivore, the greater snow goose (Chen caerulescens atlanticaL.) breeding on Bylot Island, Nunavut, Canada. During summers 2007–2009, we increased the temperature using small glasshouses (open‐top chambers, OTC) in two habitats, wetlands and mesic tundra. Every 10 days, we measured above‐ground plant biomass and a proxy of nutritive quality, nitrogen concentration, of graminoid plants in warmed and control plots from snowmelt in June until late July. Open‐top chambers increased mean maximum temperature by up to 2.0 °C in wetlands and 4.6 °C in mesic tundra. Annual warming significantly increased biomass of graminoids by up to 29% in wetlands and 20% in mesic tundra. There was no difference in nitrogen concentration of the four plant species sampled (Dupontia fisheri, Eriophorum scheuchzeri, Arctagrostis latifolia and Luzula spp.) early in the season, but the seasonal decline in nitrogen occurred more rapidly in warmed than in control plots (10% to 14% less nitrogen in warmed plots in July). This effect was consistent across the 3 years of the experiment and independent of annual variation in plant phenology. There was either a weak positive effect or no effect of the warming treatment on the nitrogen biomass of plants depending on species or period of the season. Synthesis. Our results show that warming speeds up plant phenology and the seasonal decline in nutritive quality for arctic herbivores. Because young herbivores like geese are highly sensitive to the nitrogen concentration of their food, a warmer climate will likely reduce their growth. Climate warming may therefore have a negative impact on the population dynamic of arctic herbivores by reducing the quality of their summer forage.